2020
DOI: 10.1093/jamia/ocaa024
|View full text |Cite
|
Sign up to set email alerts
|

Patient characteristics associated with objective measures of digital health tool use in the United States: A literature review

Abstract: Objective The study sought to determine which patient characteristics are associated with the use of patient-facing digital health tools in the United States. Materials and Methods We conducted a literature review of studies of patient-facing digital health tools that objectively evaluated use (eg, system/platform data representing frequency of use) by patient characteristics (eg, age, race or ethnicity, income, digital liter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(75 citation statements)
references
References 55 publications
3
59
0
Order By: Relevance
“…Collectively, these results demonstrate that although younger age and better health status jointly predict greater engagement in using eHealth for self-management, there is no generational divide in having health-related apps, accessing electronic health records, and sharing eHealth data with clinicians among cancer survivors with BMI in overweight or obese categories. Our results show agreement with mixed evidence that age is associated with eHealth use [ 34 , 35 , 37 ], and echo findings indicating that better health was associated with greater eHealth use to track health and goals [ 34 , 35 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Collectively, these results demonstrate that although younger age and better health status jointly predict greater engagement in using eHealth for self-management, there is no generational divide in having health-related apps, accessing electronic health records, and sharing eHealth data with clinicians among cancer survivors with BMI in overweight or obese categories. Our results show agreement with mixed evidence that age is associated with eHealth use [ 34 , 35 , 37 ], and echo findings indicating that better health was associated with greater eHealth use to track health and goals [ 34 , 35 ].…”
Section: Discussionsupporting
confidence: 91%
“…Individuals in the increasingly culturally and linguistically diverse survivor population may have different medical experiences, as well as different digital access and engagement [33]. The few studies [34][35][36][37] that have investigated associations among eHealth use, sociodemographic characteristics, and medical history examined the general population rather than cancer survivors. In these studies [34][35][36][37], researchers found poorer engagement in eHealth practices among adults who are older, male, in a lower annual income bracket, less healthy, or without a regular provider.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some have suggested that there is an emerging 'digital divide' where patients that lack access to computers and smartphones for a variety of reasons could miss out on health innovations that use digital technology (26). However, a recent review (albeit of few studies) reported no associations with patient characteristics (including income) and digital health tool use (27).…”
Section: Resultsmentioning
confidence: 99%
“…First, all studies need to both include diverse participants and report on race, ethnicity, educational attainment, and health and digital literacy. 13 Second, future work must focus on both internal and external validity of patient access/use of EHR data. The review by Neves et al gives us some clearer understanding of the internal validity of studies on clinical and patient-reported outcomes, but it remains unclear what impact these types of interventions will have on health outcomes across an entire healthcare system or region outside of RCT samples.…”
mentioning
confidence: 99%